Trends and Outcomes of Acute Poisoning in Felege Hiwot Comprehensive Specialized Hospital Medical Intensive Care Units: Retrospective Study [Corrigendum] - Shumet A; Shiferaw N; Mekonnen D; Asemahagn MA (Open Access Emergency Medicine, 2023)
Shumet A, Shiferaw N, Mekonnen D, Asemahagn MA. Open Access Emerg Med. 2022;14:649–656. The authors have advised there is an error in affiliations 3 and 4 on page 649. The text “Dar University” should read “Bahir Dar University”. The authors apologize for this error.